2021
DOI: 10.1007/s10803-021-05325-w
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Text Generative and Text Transcriptive Demands: Written Content and Handwriting Legibility and Speed of Children and Youth with Autism Spectrum Disorder

Abstract: The aim of this study was to assess text generation and text transcription of children and youth with Autism Spectrum Disorder (ASD, n = 67) and Typically Developing (TD) peers (n = 67). Participants (80.6% male, ages 9-14) produced a free-style handwriting task analysed for written content and handwriting legibility and speed. Findings showed children and youth with ASD perform significantly poorer than TD peers for written content and handwriting legibility and speed. For children and youth with ASD, poor ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Handwriting is a complex activity that requires higher-level cognitive functions such as working memory, planning, and organization to compose and retain text, while retrieving and activating motor programs and adjusting performance according to visual feedback (e.g., Cartmill et al, 2009;Feder & Majnemer, 2007). Since children and youth with ASD performed significantly more poorly on handwriting legibility as TD peers as shown in this study and other studies (e.g., Fuentes et al, 2009;Hellinckx et al, 2013;van den Bos et al, 2021), these results may suggest that for children with poor handwriting, longer stroke duration in air helps them to achieve better legibility by allowing them time to deal with the cognitive demands (e.g., composition, storage and retrieval of text while allocating and monitoring motor programs) of the handwriting process (Luria & Rosenblum, 2012;Werner et al, 2006). This suggestion aligns with the results of Rosenblum and colleagues (2006), who found that among TD students in the third grade, longer stroke in air duration negatively predicted handwriting product legibility of TD students without handwriting difficulties, while stroke in air duration positively predicted handwriting product legibility of TD students with handwriting difficulties.…”
Section: Model Generation -Handwriting Freestyle Tasksupporting
confidence: 75%
See 3 more Smart Citations
“…Handwriting is a complex activity that requires higher-level cognitive functions such as working memory, planning, and organization to compose and retain text, while retrieving and activating motor programs and adjusting performance according to visual feedback (e.g., Cartmill et al, 2009;Feder & Majnemer, 2007). Since children and youth with ASD performed significantly more poorly on handwriting legibility as TD peers as shown in this study and other studies (e.g., Fuentes et al, 2009;Hellinckx et al, 2013;van den Bos et al, 2021), these results may suggest that for children with poor handwriting, longer stroke duration in air helps them to achieve better legibility by allowing them time to deal with the cognitive demands (e.g., composition, storage and retrieval of text while allocating and monitoring motor programs) of the handwriting process (Luria & Rosenblum, 2012;Werner et al, 2006). This suggestion aligns with the results of Rosenblum and colleagues (2006), who found that among TD students in the third grade, longer stroke in air duration negatively predicted handwriting product legibility of TD students without handwriting difficulties, while stroke in air duration positively predicted handwriting product legibility of TD students with handwriting difficulties.…”
Section: Model Generation -Handwriting Freestyle Tasksupporting
confidence: 75%
“…Given the sample size of the current study, the authors had to limit themselves on the number of potential predictors that could be included in the handwriting models for both handwriting tasks. Several studies have suggested that in addition to the different predictors of handwriting analyzed in this study, linguistic functions such as verbal memory or reading are associated with different handwriting product characteristics (e.g., Cartmill et al, 2009;Dockrell et al, 2014) and predict handwriting legibility and speed (Van den Bos et al, 2021). Future studies with sufficiently large sample sizes should include linguistic variables to determine the relative effect of linguistic functions as a predictor of the handwriting difficulties of children and youth with ASD.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 91%
See 2 more Smart Citations